Reformulasi Kebijakan Kriminal dalam Penanggulangan Kejahatan Berbasis Teknologi Kecerdasan Buatan (SETARA : Jurnal Ilmu Hukum, 2024)
The reformulation of criminal policy in combating artificial intelligence (AI)-based crime has become an urgent issue as technology develops rapidly. This study examines legal challenges related to digital crime, regulatory strengthening, and the role of law enforcement institutions in addressing these problems. The method used is a literature study with a qualitative approach. The study finds the need for AI-specific regulation, the establishment or strengthening of institutions competent in technology, and international cooperation in combating AI-based crime. Such policy reform is expected to create a legal system that is more responsive to digital threats.